2011
DOI: 10.4103/0973-1482.82928
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of serum fucose in oral squamous cell carcinoma patients

Abstract: Serum fucose can be used as an effective diagnostic biomarker in oral squamous cell carcinoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…In this study we observed a very high serum fucose in OSMF, Leukoplakia and OC, when compared to controls ( P < 0.001) as like that was observed by Parwani RN et al 28. in their study.…”
Section: Discussionsupporting
confidence: 89%
“…In this study we observed a very high serum fucose in OSMF, Leukoplakia and OC, when compared to controls ( P < 0.001) as like that was observed by Parwani RN et al 28. in their study.…”
Section: Discussionsupporting
confidence: 89%
“…They reported over 2-fold increase in serum glycoprotein L-fucose in patients compared to controls. Findings reported by other researchers are also consistent (29,30). However, according to our best knowledge, this study, for the first time, demonstrates that HNSCC-induced alterations in fucose levels can be also detected in unstimulated whole-mouth saliva.…”
Section: Discussionsupporting
confidence: 90%
“…Serum fucose level in the present study was significantly found to be elevated among cancer patients (46.63 ± 5.29 mg/dl) when compared to control group (7.22 ± 0.26 mg/dl) as observed by Parwani and Parwani,[ 14 ] Bose et al . [ 15 ] in their study.…”
Section: Discussionsupporting
confidence: 72%
“…In this study, the normal fucose level in the control group is 7.22 ± 0.26 mg/dl. In contrast, to the established normal fucose level by Parwani RN and Parwani SR[ 14 ] was found 5.32 ± 0.67 mg/dl.…”
Section: Discussionmentioning
confidence: 72%